TOTAL LYMPHOCYTE COUNT AS A SUBSTITUTE TO CD4 COUNT IN MANAGEMENT OF HIV INFECTED INDIVIDUALS IN RESOURCE LIMITED SOCIETY - Daud, Muhammad Yousuf; Qazi, Rizwan Aziz; Bashir, Naila (Journal of Ayub Medical College Abbottabad, 2015)
Background: Pakistan is a resource limited society and gold standard parameters to monitor HIV disease activity are very costly. The objective of the study was to evaluate total lymphocyte count (TLC) as a surrogate to CD4 count to monitor disease activity in HIV/AIDS in resource limited society. Methods: This cross sectional study was carried out at HIV/AIDS treatment centre, Pakistan Institute of Medical Sciences (PIMS), Islamabad. A total of seven hundred and seventy four (774) HIV positive patients were enrolled in this study, and their CD4 count and total lymphocyte count were checked to find any correlation between the two by using Spearman ranked correlation coefficient. Results: The mean CD4 count was (434.30±269.23), with minimum CD4 count of (9.00), and maximum of (1974.00). The mean total lymphocyte count (TLC) was (6764.0052±2364.02) with minimum TLC (1200.00) and maximum TLC was (20200.00). Using the Pearson's correlation (r) there was a significant and positive correlation between TLC and CD4 count. (r2=0.127 and p=0.000) at 0.01 level. Conclusion: Our study showed a significant positive correlation between CD4 count and total lymphocyte count (TLC), so TLC can be used as a marker of disease activity in HIV infected patients. Keywords: HIV (human immunodeficiency virus), CD4 count, Total lymphocyte count (TLC).